Convolutional Neural Networks for Pneumonia Detection: A Preliminary Investigation and Development Framework - Muhammad Faiz Anuar; Siti Munirah Mohd; Nurhidaya Mohamad Jan; Anucha Watcharapasorn (Penerbit Citra Lestari, 2025)
Non Indexed Publication (Tier 4)